Rachunkowość a upadłość - Szczerbiński, Andrzej (Accounting in Bankruptcy, 2005)
The bankruptcy declaration affects entrepreneur's accounting proceeded according to the Accountancy Act. At the moment of bankruptcy declaration, an official receiver or a forced manager becomes a company's chief, responsible for the fulfillment of accountancy obligations. The aim of the paper is to define these obligations in the context of the Accountancy Act and Bankruptcy Act.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 261-265